Stochastic models and their solution in MS Excel - Müller, Jan; Kořenář, Václav, 1944-; Pelikán, Jan, 1943-; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2010)
The aim of this thesis is to create an application in MS Excel, which would have been able to count on basic stock models, and Markov decision processes with alternatives. This issue is devoted to the first part of the work. This is the theory needed to understand the basic principles and method of calculation tasks. The second part describes the developed application that can be solved one-product and multiproduct deterministic stock models, stochastic stock models and Markov decision processes with alternatives, and changing valuation of the transition. The description is supplemented with graphic images directly from the application, which makes using applications easier to understand. The part of work is also CD with created application.
Vedoucí práce: Václav Kořenář
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2010
Rok obhajoby 2010
Keywords: ekonometrie a operační výzkum [obor dipl. práce]; diplomové práce; master's theses